The difference between IgM and IgG antibody prevalence in different serological assays for COVID-19; lessons from the examination of healthcare workers - Kobashi, Yurie (Int Immunopharmacol, 2021)
OBJECTIVES: The objective of this study was to investigate the differences between the results of two serology assays for detection of COVID-19 among medical staff, who are at higher risks of infection. METHODS: The immunochromatography (ICG) rapid test kit and the chemiluminescence immunoassay (CLIA) quantitative antibody test were performed. The differences in IgM and IgG antibody prevalence in different serological assays were descriptively analyzed. RESULTS: A total of 637 participants were included in this research. Two staff were IgM positive in the CLIA quantitative antibody test (cutoff value: 10 AU/ml) of 51 staff who were IgM positive in the rapid test kit. Six staff were IgG positive in the CLIA quantitative antibody test of 56 staff who were IgG positive in the rapid test kit. The proportion of antibody positive staff differed greatly between the rapid test kit and the CLIA quantitative antibody test. CONCLUSIONS: There was a vast difference in the proportions of IgG and IgM antibody positive staff in the rapid test kit and the CLIA quantitative antibody test results. The results from the only rapid test kit might have to be interpreted with caution. Further studies to evaluate antibody testing accuracy are required to promote the understanding of each assay's characteristics and determine their purposes in each community.